ORGANISATIONAL CRISES IN THE HOTEL SECTOR: A PERSPECTIVE FROM SINGAPORE - HENDERSON, JOAN C. (ITB Journal Publisher, LPPM ITB, 2008)
Crises in the tourism and hospitality industry are a topic of some concern in view of their increasing prevalence in the modern world. Planning for and handling such situations has thus become essential and this paper discusses issues of organisational crises and their management with specific reference to hotels in Singapore. Case studies of selected properties based on interviews with general managers are analysed and overall conclusions are presented about perceptions, origins and impacts of crises. Insights are also afforded into strategies for dealing with crises and the importance of planning and learning lessons from previous experiences are highlighted.